High density lipoprotein particle size and function associate with new cardiovascular events in patients with chronic kidney disease - Anna V Mathew; Yun Han; Vetalise C Konje; Yanhong Guo; Jaeman Byun; Alexander George; Julian Meza; Sanjay Rajagopalan; Y. Eugene Chen; Brenda Gillespie; Rajiv Saran; Subramaniam Pennathur (PLoS ONE, 2025)
Chronic Kidney Disease (CKD) is a risk factor for cardiovascular disease (CVD), and patients with CKD have markedly higher CVD mortality compared to healthy controls. However, the relationship between specific lipoprotein profiles and new CV events in patients with advanced CKD and cardiovascular burden is unknown. We profiled the distribution of High density lipoprotein (HDL) size, particle concentration, and cholesterol and triglyceride content of the baseline plasma of 325 subjects with moderate CKD followed for 2.5 years using nuclear magnetic resonance (NMR) spectroscopy. We used Cox regression models controlled for various clinical factors to characterize the role of specific HDL profiles in predicting CV events in this high-risk population. The cholesterol uptake capacity of HDL from peripheral tissues- cholesterol efflux capacity (CEC) and HDL oxidation were also quantified using standardized assays. Patients with new CV events demonstrated increased HDL size, large HDL particle numbers, and CEC. Increased HDL particle size [HR = 2.56, p = 0.002], large HDL particle numbers [HR = 1.41, p = 0.001], HDL-cholesterol levels [HR = 1.03, p = 0.008], and CEC [HR = 1.46, p = 0.03] associated with CV events. Our study demonstrates that higher HDL particle size associated with new CV events in the CKD population with a high cardiovascular burden independent of CEC and HDL cholesterol. Collectively, the data strongly associate altered lipoprotein metabolism, particularly HDL metabolism, and new CV events in patients with established CKD and CVD, allowing us to risk stratify and potentially reduce mortality and morbidity in this high-risk population.